Effect of agronomic practices on productivity and profitability of anise (Pimpinella anisum L.) - S S Meena, R S Mehta, G Lal, M M Anwer, S S Meena, R S Mehta, G Lal, M M Anwer (Journal of Spices and Aromatic Crops, 2012)
A field experiment was carried out at Ajmer (Rajasthan) to find out the optimum sowing time and crop geometry for realising higher productivity and profitability in anise (Pimpinella anisum L.). Fifteen treatment combinations comprising of five dates of sowing viz., 15th October, 30th October, 15th November, 30th November and 15th December in main plot and three crop geometry viz., 20 cm × 10 cm, 25 cm × 10 cm and 30 cm × 10 cm spacing in sub plot were taken. The results revealed that sowing of anise on 15th October produced significantly higher plant height (7.94 cm, 40.98 cm and 54.88 at 60,90 DAS and at harvest, respectively), number of branches plant-1 (14.70 and 13.92 at 90 DAS and harvest respectively), number of umbels plant-1 (40.91), number of umbellates umbel-1 (17.4), number of seeds umbellate-1 (19.45), test weight (2.60 g), seed yield (892 kg ha 1), gross returns (Rs. 80,280 ha-1), net returns (Rs. 74,280 ha-1) and benefit: cost ratio (12.38). Crop geometry of 20 cm × 10 cm significantly resulted in highest plant height, number of branches plant-1 at all stages, number of umbels plant-1 (31.57), number of umbellates umbel-1 (14.72), number of seeds per umbellate (17.58), test weight (2.40 g), seed yield (507 kg ha-1), net returns (Rs. 39630 ha-1) and Benefit Cost Ratio (6.61). Therefore, sowing of anise on I5th October at 20 cm × 10 cm spacing was optimum for realising higher productivity and profitability of the crop.